The sirens of Baghdad : a novel - Khadra, Yasmina; Cullen, John, 1942- (New York : Nan A. Talese/Doubleday, 2007)
Forced to leave the university when the Americans invade Iraq, a young man from a small desert village heads for Baghdad to join the resistance, until a top secret mission forces him to reconcile a proposed terrorist act with his own moral principles.
Keywords: Baghdad (Iraq) -- Fiction